2011
DOI: 10.1111/j.1439-0426.2011.01802.x
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive biology of the freshwater goby Knipowitschia croatica Mrakovčić, Kerovec, Mišetić & Schneider 1996 (Actinopterygii, Gobiidae)

Abstract: The reproductive biology and gonadogenesis cycle of the Vrgorac goby, Knipowitschia croatica is described [Conservation of Endangered Freshwater Fish in Europe, Birkhauser Verlag, Basel]. The species displays sexual dimorphism during the spawning period. Sexual maturity is achieved at an early age, with 50% of males and females sexually mature at total lengths of 40-45 mm. Fecundity of gravid females ranged from 188 to 593 eggs, with an egg diameter of 0.22-1.11 mm. Though the extended spawning period lasts fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 10 publications
2
13
0
4
Order By: Relevance
“…The black-spot goby is a small sized fish; the observed maximum length SL = 3.8 cm in this study is lower than the observed values in the range area reaching a maximum standard size length (SL) of 6.7 cm (Miller, 1986). This data coincides with the Matica River (Croatia) population of Knipowithscia croatica, a similar short-lived goby (Zanella et al, 2011). This data coincides with the Matica River (Croatia) population of Knipowithscia croatica, a similar short-lived goby (Zanella et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The black-spot goby is a small sized fish; the observed maximum length SL = 3.8 cm in this study is lower than the observed values in the range area reaching a maximum standard size length (SL) of 6.7 cm (Miller, 1986). This data coincides with the Matica River (Croatia) population of Knipowithscia croatica, a similar short-lived goby (Zanella et al, 2011). This data coincides with the Matica River (Croatia) population of Knipowithscia croatica, a similar short-lived goby (Zanella et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…As the species from the genus Pomatoschistus are thought to live up to 2 years (Kottelat and Freyhof, 2007), according to length categories we can assume that the specimens were in the beginning of their second year of life (1+). This data coincides with the Matica River (Croatia) population of Knipowithscia croatica, a similar short-lived goby (Zanella et al, 2011).…”
Section: Discussionsupporting
confidence: 85%
“…Studies on the reproductive biology of the family Gobiidae are very few in number. The most notable contributions in this regard are that of, Miller, ; Chesalin, Zuev, & Chesalin, ; La Mesa, Arneri, Caputo, & Lylesias, ; Islam & Joadder, ; Kovacic, ; Kovac, Copp, & Sousa, ; Zanella et al, ; Gkenas & Leonardos, ; Islam & Mollah, ; Hossain, ; Durin, Kohinoor, Mominuzzaman, & Shirajum, .…”
Section: Introductionmentioning
confidence: 99%
“…Subadults and adults feed on benthic invertebrates (Gandolfi et al 1991, Bruno & Maugeri 1992, Zerunian 1998, 2002a, 2002b, 2003, 2004, Kottelat & Freyhof 2007, Porcellotti 2005, Fortini 2016). The reproductive biology of O. punctatissimus is similar to that of O. croaticus, studied by Zanella et al (2011). O. punctatissimus reaches a maximum length of 55 mm TL (mostly 20-40 mm TL when mature).…”
Section: Ecology and Biologymentioning
confidence: 64%